Ответы и объяснения

2013-05-23T00:43:06+04:00
14) lg(x-4) + lg(2x-1) = lg9
Lg(x-4)*(2x-1) = lg9
Lg(2x^2 - 9x + 4) = lg9
2x^2 - 9x + 4 = 9
2x^2 - 9x - 5 = 0
D = 121
X = 5, x = -1/2 (не подходит, так как отриц.)
Ответ: 5
17) log^2 5 x - 3 log 5 x - 4 = 0
Log 5 x = t
t^2 - 3t - 4 = 0
D = 25
t = 4 => log 5 x = 4 => x = 5^4 = 625
t = - 1 => log 5 x = -1 => x = 5^-1 = 1/5
Ответ: 625, 1/5
22) log 81 x + log 81 (x-6) = log 81 27
Log 81 (x^2 - 6x) = log 81 27
X^2 - 6x - 27 = 0
D = 144
X = 9, x = -3 (отриц. не подходит)
Ответ: 9